Oil palm plantation is not a suitable environment for most forest specialist species of Odonata in Amazonia. (30th June 2018) - Carvalho, F. G.; de Oliveira Roque, F.; Barbosa, L.; de Assis Montag, L. F.; Juen, L.
Abstract: Oil palm monoculture is the most rapidly increasing large‐scale crop in Amazonia due to favourable environmental conditions and incentives from executives and governing authorities. In this study we assessed the effects of oil palm plantations on Odonata assemblages in Amazonia streams. We hypothesized that (1) the expansion of oil palm plantations over the natural landscape affects the habitat structure and physicochemical properties of streams at different scales (50 m, 500 m and 1000 m) and (2) oil palm plantations affect the species composition of Odonata assemblages, leading to the replacement of forest specialist species by non‐forest specialists. A total of 22 streams were sampled which were distributed throughout a landscape comprising areas of oil palm plantations Elaeis guineensis Jacq. to streams located inside large forest remnants. The expansion of oil palm monoculture affected the physicochemical properties of the water and habitat of the streams. A larger amount of woody debris was observed within streams surrounded by a greater amount of forest, whereas streams with a greater area of surrounding oil palm had higher pH values and anthropogenic infrastructures (e.g. roads). As expected, the Odonata community was affected by a replacement of forest specialist species with non‐forest specialist species. To mitigate this impact, we suggest increasing the area of native riparian corridors along streams that flow through oil palm plantations. Abstract : Orthemis discolor (photo) is a species of the family of dragonflies known as Libellulidae. It is found in Central America, North America and South America. In general, the organisms of this species are considered habit generalist, as it presents a wide range of living conditions. The IUCN status of the O. discolor is less worrying, with no immediate threat to the species' survival and the population is stable.